Determinan Penyakit Hipertensi Di Kelurahan Sungai Besar Kota Banjarbaru - Amalia Amalia; Ardi Juliandatama; Hilda Irianty (Wal'afiat Hospital Journal, 2021)
According to data obtained at the Sungai Besar Village Health Center in 2017, there were 2237 cases of hypertension. At the time of the preliminary study by interviewing 10 respondents there were 6 people who had hypertension caused by food factors while 4 people were caused by stress factors and family history. Hypertension is a health disorder where this condition cannot be cured but can be controlled with a lifestyle. The purpose of this study was to determine and analyze the relationship (Stress, Diet and Nutritional Status) with hypertension in Sungai Besar Village, Banjarbaru City. The population taken from this study was 1925 people, and the sample of this study was 95 people using the Slovin formula and accidental sampling technique. This type of research is analytical research with a quantitative approach method. To analyze the factors that cause hypertension. The instruments or tools used in the research are in the form of questionnaires and interviews. Data analysis consisted of univariate analysis and bivariate analysis. The results of the study showed that there was a relationship between stress (p=0.000) and diet (p=0.000) with hypertension, while there was no relationship between nutritional status (p=0.303) and hypertension. It is recommended for the community to always control their lifestyle and check their health to the nearest health service.